2014
DOI: 10.1603/ec14080
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Patterns in <I>Coptotermes gestroi</I> (Blattodea: Rhinotermitidae) Following Horizontal Transfer of Nonrepellent and Repellent Insecticides: Effects of Donor:Recipient Ratio and Exposure Time

Abstract: The donor: recipient ratio and the time of donor exposure to termiticide required for maximal toxicant transfer among termites are crucial information for the development of termite management plans. Most of the available information on termiticide toxicity came from temperate zonal termite species, whereas little is known about tropical Asian species. In this study, mortality patterns of recipient termites, Coptotermes gestroi (Wasmann) subjected to seven formulated insecticide exposures under different donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Yet, chlorpyrifos is not preferred for termite control because neonicotinoid pesticides and their mammalian toxicities are generally low and show low acute toxicities to birds and fish compared to other common pesticide groups. Chlorpyrifos, though, displayed significant toxicities to bees (Parman and Vargo 2010;Neoh et al 2014;Rondeau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, chlorpyrifos is not preferred for termite control because neonicotinoid pesticides and their mammalian toxicities are generally low and show low acute toxicities to birds and fish compared to other common pesticide groups. Chlorpyrifos, though, displayed significant toxicities to bees (Parman and Vargo 2010;Neoh et al 2014;Rondeau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies considering the transfer of chlorfenapyr under laboratory conditions have had mixed results with some evidence suggesting that transfer might be a significant source of mortality in the field. Transfer of chlorfenapyr between nestmate termites has been observed in several species (Rust & Saran, 2006;Shelton et al, 2006;Neoh et al, 2014). In Heterotermes indicola (Wasmann), a species in the same genus as H. aureus, chlorfenapyr transfer was only evident at very low concentration (Misbah-Ul-Haq et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Formulations containing fipronil are sold under the trade names Termidor (BASF, Florham Park, NJ, USA), Ultrathor (Ensystex, Auburn, NSW, Australia), and Taurus (Control Solutions Inc., Pasadena, TX, USA). Laboratory research has shown that horizontal transfer of fipronil occurs in a variety of termite species (Saran & Rust, 2007;Spomer et al, 2008;Neoh et al, 2014). Furthermore, a few field studies have reported distance effects of fipronil soil application on termite presence near structures in the eastern subterranean termite, Reticulitermes flavipes (Kollar) (Potter & Hillery, 2002;Vargo & Parman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…effectively in vineyards and citrus groves including the organophosphates chlorpyrifos and terbufos and the pyrethroid α-cypermethrin (Addison, 2002;James, Stevens, & O'Malley, 1998;Klotz et al, 2003). Non-repellent contact insecticides allow the insect species to acquire the toxicant without detecting it and then transfer it horizontally to other fit nestmates (Neoh, Yeoh, & Lee, 2014;Rust, Reierson, & Klotz, 2003;Shelton & Grace, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bifenthrin is used by urban pest management personnel as a barrier treatment around homes, hospitals, nursing facilities and in electrical casing, targeting termites and ants including the invasive ant species L. humile and Solenopsis invicta (Choe & Rust, 2008;Klotz, Rust, Costa, & Reierson, 2002;Neoh et al, 2014;Pranschke, Hooper-Bùi, & Moser, 2003). Bifenthrin (Fig.…”
Section: Introductionmentioning
confidence: 99%